Postal IEDs and risk assessment of work health and safety considerations for postal workers. (15th July 2019) - Grant, Matthew; Stewart, Mark G.
Postal improvised explosive devices (IEDs) provide criminals and terrorists with a convenient mechanism for delivering an energetic payload to an intended victim with little operational risk. Postal IEDs formed 7% of IED attacks reported in the West between 1998-2015, are often dispatched in groups and can bring postal systems to a standstill. Nearly 30% of postal IED explosions occur in the postal worker environment and a third of the casualties caused by postal IEDs are postal workers. Postal IEDs are debatably a reasonably foreseeable cause of harm to postal workers and should be considered under the work health and safety (WHS) constructs of many Western nations. This paper considers this problem, using a probabilistic risk assessment model to inform a cost-benefit analysis considering potential risk reduction options for postal workers. It identifies that the control measures identified were not cost-effective where only the direct WHS costs pertaining to unintentional postal IED detonation within the mail delivery system were considered given the risk levels identified.